2019
DOI: 10.1098/rsos.181186
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal brain stimulation during food-related inhibition training: effects on food craving, food consumption and inhibitory control

Abstract: Modulation of dorsolateral prefrontal cortex (DLPFC) activity using non-invasive brain stimulation has been shown to reduce food craving as well as food consumption. Using a preregistered design, we examined whether bilateral transcranial direct current stimulation (tDCS) of the DLPFC could reduce food craving and consumption in healthy participants when administered alongside the cognitive target of inhibitory control training. Participants (N = 172) received either active or sham tDCS (2 mA; anode F4, cathod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 94 publications
(160 reference statements)
1
41
0
Order By: Relevance
“…However, as the number of studies utilizing tDCS in the exploration of its effects on food craving has increased, evidence of efficacy has weakened. A more recent meta-analysis, including eight experiments, found no effect of tDCS on food craving [386], and subsequent research, including a large pre-registered experiment, has also failed to replicate findings for both food craving and consumption [435,436].…”
Section: Treatment Implicationsmentioning
confidence: 99%
“…However, as the number of studies utilizing tDCS in the exploration of its effects on food craving has increased, evidence of efficacy has weakened. A more recent meta-analysis, including eight experiments, found no effect of tDCS on food craving [386], and subsequent research, including a large pre-registered experiment, has also failed to replicate findings for both food craving and consumption [435,436].…”
Section: Treatment Implicationsmentioning
confidence: 99%
“…NIBS may enhance synaptic strength in neuronal pathways activated by cognitive training, amplifying effects of training and thus cognitive bias modification efficacy 64. As the effectiveness of tDCS may thus be improved by pairing administration with a cognitive task inducing activity in the target brain region,65–67 such combined treatment interventions have been investigated among alcohol dependent inpatients (ABM and tDCS),68 and to enhance inhibitory control related to food consumption (Go/No-Go Task and tDCS) 65. The insignificant findings from these studies warrant commentary that to date, studies that have found positive effects of tDCS have either included obese participants or have had multi-session protocols 65 69–71.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to control one’s actions and thoughts is important for our daily lives; for example: changing gait when there is an obstacle in the path 1 , resisting the temptation to eat when on a diet 2 , overcoming the tendency to say something hurtful 3 . While many processes contribute to such forms of control, one important process is response inhibition – the prefrontal (top-down) stopping of initiated response tendencies 4 .…”
mentioning
confidence: 99%